Analyse der Analogiebildung in kontextorientierten Lernumgebungen - Wedekind, Lisa; Pollmeier, Pascal; Fechner, Sabine (Frühe naturwissenschaftliche Bildung)

Coherent Swing‐Up Excitation for Semiconductor Quantum Dots - Boos, Katarina; Sbresny, Friedrich; Kim, Sang Kyu; Kremser, Malte; Riedl, Hubert; Bopp, Frederik W.; Rauhaus, William; Scaparra, Bianca; Jöns, Klaus; Finley, Jonathan J.; Müller, Kai; Hanschke, Lukas (Advanced Quantum Technologies)
Abstract Developing coherent excitation methods for quantum emitters ensuring high brightness, optimal single‐photon purity and indistinguishability of the emitted photons has been a key challenge in the past years. While various methods have been proposed and explored, they all have specific advantages and disadvantages. This study investigates the dynamics of the recent swing‐up scheme as an excitation method for a two‐level system and its performance in single‐photon generation. By applying two far red‐detuned laser pulses, the two‐level system can be prepared in the excited state with near‐unity fidelity. The successful operation and coherent character of this technique are demonstrated using a semiconductor quantum dot (QD). Moreover, the multi‐dimensional parameter space of the two laser pulses is explored to analyze its impact on excitation fidelity. Finally, the performance of the scheme as an excitation method for generating high‐quality single photons is analyzed. The swing‐up scheme itself proves effective, exhibiting nearly perfect single‐photon purity, while the observed indistinguishability in the studied sample is limited by the influence of the inevitable high excitation powers on the semiconductor environment of the quantum dot.

Experimental measurement of the reappearance of Rabi rotations in semiconductor quantum dots - Hanschke, L.; Bracht, T. K.; Schöll, E.; Bauch, David; Berger, Eva; Kallert, Patricia; Peter, M.; Garcia, A. J.; Silva, S. F. Covre da; Manna, S.; Rastelli, A.; Schumacher, Stefan; et al. (arXiv:2409.19167)
Phonons in solid-state quantum emitters play a crucial role in their performance as photon sources in quantum technology. For resonant driving, phonons dampen the Rabi oscillations resulting in reduced preparation fidelities. The phonon spectral density, which quantifies the strength of the carrier-phonon interaction, is non-monotonous as a function of energy. As one of the most prominent consequences, this leads to the reappearance of Rabi rotations for increasing pulse power, which was theoretically predicted in Phys. Rev. Lett. 98, 227403 (2007). In this paper we present the experimental demonstration of the reappearance of Rabi rotations.

Purcell-enhanced single-photon emission from InAs/GaAs quantum dots coupled to broadband cylindrical nanocavities - Jöns, Klaus
On-chip emitters that can generate single and entangled photons are essential building blocks for developing photonic quantum information processing technologies in a scalable fashion. Semiconductor quantum dots (QDs) are attractive candidates that emit high-quality quantum states of light on demand, however at a rate limited by their spontaneous radiative lifetime. In this study, we utilize the Purcell effect to demonstrate up to a 38-fold enhancement in the emission rate of InAs QDs by coupling them to metal-clad GaAs nanopillars. These cavities, featuring a sub-wavelength mode volume of 4.5x10-4 (λ/n)3 and low quality factor of 62, enable Purcell-enhanced single-photon emission across a large bandwidth of 15 nm. The broadband nature of the cavity eliminates the need for implementing tuning mechanisms typically required to achieve QD-cavity resonance, thus relaxing fabrication constraints. Ultimately, this QD-cavity architecture represents a significant stride towards developing solid-state quantum emitters generating near-ideal single-photon states at GHz-level repetition rates.

Typiken zum fachspezifischen Umgang mit Anforderungssituationen diagnosegeleiteter Förderung. Professionalisierung von fachfremd unterrichtenden Lehrkräften zur diagnosegeleiteten Förderung im inklusiven Mathematikunterricht am Beispiel der Förderung von Operationsvorstellungen - Graf, Lara Marie; Häsel-Weide, Uta; Höveler, K.; Nührenbörger, M. (Empirische Sonderpädagogik)

Analyse des Modellierprozesses von Grundschüler*innen zum Thema Löslichkeit - Elsner, Julia; Tenberge, Claudia; Fechner, Sabine (In Alternativen denken - Kritik, Reflexion und Transformation im Sachunterricht)
Die Autorinnen untersuchen im Rahmen ihrer Prä-Post-Studie mit Viertklässlern, ob der Modellierungsprozess durch analoges Schließen zwischen mehreren Phänomenen unterstützt werden kann, und ob chemische Konzepte zum Thema Löslichkeit erlernt werden können. Die Ergebnisse zeigen, dass Grundschüler*innen ihre mentalen Modelle in einem Modell ausdrücken und teilweise revidieren können. In einigen Fällen werden die Modelle reflektiert und Grenzen erkannt. (DIPF/Orig.)

Editorial: Was ist literaturwissenschaftliche Ideengeschichte? - Heise, Tillmann; Gräf, Kai (Scientia Poetica)

High-throughput antibody screening with high-quality factor nanophotonics and bioprinting

Schottky-barrier type infrared photodetector - Güsken, Nicholas Alexander

Inference serving with end-to-end latency SLOs over dynamic edge networks - Nigade, Vinod; Bauszat, Pablo; Bal, Henri; Wang, Lin (Real-Time Systems)
Abstract While high accuracy is of paramount importance for deep learning (DL) inference, serving inference requests on time is equally critical but has not been carefully studied especially when the request has to be served over a dynamic wireless network at the edge. In this paper, we propose Jellyfish—a novel edge DL inference serving system that achieves soft guarantees for end-to-end inference latency service-level objectives (SLO). Jellyfish handles the network variability by utilizing both data and deep neural network (DNN) adaptation to conduct tradeoffs between accuracy and latency. Jellyfish features a new design that enables collective adaptation policies where the decisions for data and DNN adaptations are aligned and coordinated among multiple users with varying network conditions. We propose efficient algorithms to continuously map users and adapt DNNs at runtime, so that we fulfill latency SLOs while maximizing the overall inference accuracy. We further investigate dynamic DNNs, i.e., DNNs that encompass multiple architecture variants, and demonstrate their potential benefit through preliminary experiments. Our experiments based on a prototype implementation and real-world WiFi and LTE network traces show that Jellyfish can meet latency SLOs at around the 99th percentile while maintaining high accuracy.

Erhebung und Förderung digitalisierungsbezogener Kompetenzen von Chemielehrkräften - Ponath, Jonas; Pollmeier, Pascal; Fechner, Sabine (Jahrestagung der Gesellschaft für Didaktik der Chemie und Physik e.V.)
Keywords: Digital; Digitalisierung; Künstliche Intelligenz; KI; Messsensoren; Lehrkräfte; Chemie; Kompetenzen

Leitbild des Profibereichs Transformation und Bildung - Buhl, Heike M.; Fechner, Sabine; Herzig, Bardo; Jenert, Tobias; Kremer, H. - Hugo; Rohlfing, Katharina Justine; Vogelsang, Christoph

Pyroelectric influence on lithium niobate during the thermal transition for cryogenic integrated photonics - Thiele, Frederik; Hummel, Thomas; Lange, Nina Amelie; Dreher, Felix; Protte, Maximilian; Bruch, Felix vom; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Materials for Quantum Technology)
Abstract Lithium niobate has emerged as a promising platform for integrated quantum optics, enabling efficient generation, manipulation, and detection of quantum states of light. However, integrating single-photon detectors requires cryogenic operating temperatures, since the best performing detectors are based on narrow superconducting wires. While previous studies have demonstrated the operation of quantum light sources and electro-optic modulators in LiNbO 3 at cryogenic temperatures, the thermal transition between room temperature and cryogenic conditions introduces additional effects that can significantly influence device performance. In this paper, we investigate the generation of pyroelectric charges and their impact on the optical properties of lithium niobate waveguides when changing from room temperature to 25 K, and vice versa. We measure the generated pyroelectric charge flow and correlate this with fast changes in the birefringence acquired through the Sénarmont-method. Both electrical and optical influence of the pyroelectric effect occur predominantly at temperatures above 100 K.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Der digitale Erste-Hilfe-Koffer - Unterstützung von Studierenden der Ernährungslehre im Bereich Chemie - Elsner, Julia; Buyken, Anette E.; Schulte, Eva Andrea; Fechner, Sabine (Lehkräftebildung in der digitalen Welt - Zukunftsorientierte Forschungs- und Praxisperspektiven)

Plasmonic modulators: bringing a new light to silicon - Hoessbacher, C.; Baeuerle, B.; Del Medico, N.; De Leo, E.; Güsken, Nicholas Alexander; Heni, W.; Langenbach, A.; Tedaldi, V. (IET Conference Proceedings)

Electrifying the field of metasurface optics - Güsken, Nicholas Alexander; Brongersma, Mark L. (Photonics Insights)

Medienbezogene Vorerfahrungen und Voraussetzungen von Lehramtsstudierenden zu Beginn ihres Studiums Analysen aus Evaluationsbefragungen an der Universität Paderborn vor und nach der COVID-19-Pandemie - Vogelsang, Christoph; Schwabl, Franziska (Lehrkräftebildung in der digitalen Welt. Zukunftsorientierte Forschungs- und Praxisperspektiven)

Scalable quantum detector tomography by high-performance computing - Schapeler, Timon; Schade, Robert; Lass, Michael; Plessl, Christian; Bartley, Tim (Quantum Science and Technology)
At large scales, quantum systems may become advantageous over their classical counterparts at performing certain tasks. Developing tools to analyze these systems at the relevant scales, in a manner consistent with quantum mechanics, is therefore critical to benchmarking performance and characterizing their operation. While classical computational approaches cannot perform like-for-like computations of quantum systems beyond a certain scale, classical high-performance computing (HPC) may nevertheless be useful for precisely these characterization and certification tasks. By developing open-source customized algorithms using high-performance computing, we perform quantum tomography on a megascale quantum photonic detector covering a Hilbert space of 106. This requires finding 108 elements of the matrix corresponding to the positive operator valued measure (POVM), the quantum description of the detector, and is achieved in minutes of computation time. Moreover, by exploiting the structure of the problem, we achieve highly efficient parallel scaling, paving the way for quantum objects up to a system size of 1012 elements to be reconstructed using this method. In general, this shows that a consistent quantum mechanical description of quantum phenomena is applicable at everyday scales. More concretely, this enables the reconstruction of large-scale quantum sources, processes and detectors used in computation and sampling tasks, which may be necessary to prove their nonclassical character or quantum computational advantage.

Level Up! Gamification in der Lehrkräfteausbildung - Konzeption und Erfahrung eines gamifizierten Seminars in der Hochschullehre für Lehramtsstudierende - Truong, Ha My (Lehrkräftebildung in der digitalen Welt. Zukunftsorientierte Forschungs- und Praxisperspektiven)
Game-based Learning (GBL) und Gamification (GF) gewinnen im schulischen Umfeld zunehmend an Bedeutung. Ihr Einsatz bietet die Möglichkeit, eigenverantwortliches Lernen im Unterricht zu fördern, bringt aber auch Herausforderungen für Lehr- und Lernprozesse mit sich. Daher ist es von großer Bedeutung, angehenden Lehrkräften die notwendigen Kompetenzen zu vermitteln, um GBL und GF effektiv in den Unterricht zu integrieren. Vor diesem Hintergrund wurde ein Lehrkonzept für die Hochschullehre entwickelt und hinsichtlich der Zielerreichung evaluiert. Der vorliegende Beitrag gibt einen Einblick in die Gestaltungsaspekte des Seminars sowie erste Erkenntnisse und Erfahrungen der Studierenden.
Keywords: Game-based learning; Gamification; Hochschullehre; Lehrkräftebildung

Research on curriculum resources in mathematics education: a survey of the field - Rezat, Sebastian (ZDM – Mathematics Education)
Abstract This survey describes the structure of the field of research on curriculum resources in mathematics education in the period from 2018 till 2023. Based on the procedures of a systematic review relevant literature was identified using Web of Science as a database. The included literature was analyzed and categorized according to the type of curriculum resource and the area of study. Seven areas of studies were identified: studies on the role of curriculum resources, content analysis, user studies, studies on the effects of curriculum resources, studies on curriculum resource design, curriculum resources as data, and reviews. The areas were further subdivided into different subcategories based on the research questions of the included papers. The findings show that research on mathematics textbooks is still predominant in the field. The most popular areas of research are content analysis, user studies, studies on design, and studies on effects. Emerging areas are research on students’ use of curriculum resources and the employment of user data from digital curriculum resources as data basis in mathematics education research.